2012
DOI: 10.7773/cm.v38i3.2094
|View full text |Cite
|
Sign up to set email alerts
|

Growth, feed intake, survival, and histological response of white shrimp Litopenaeus vannamei fed diets containing grains naturally contaminated with aflatoxin

Abstract: INTRODUCCIÓNEl objetivo final de los fabricantes y proveedores de alimento acuícola es asegurar que los alimentos producidos sean seguros y saludables (Tacon y Metian 2008 ABSTRACT. Two feeding trials were carried out to evaluate the effect of diets containing corn or peanut grains naturally contaminated with aflatoxins on the growth, feed intake, survival, and histological response of the white shrimp Litopenaeus vannamei. In trial 1, four experimental diets were formulated to contain 0, 500, 1000, and 2000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 17 publications
3
13
0
4
Order By: Relevance
“…Reduction in feed intake might be caused by the presence of non-palatable compounds generated in the grain during mold growth. No reduction in survival was found in the present study using low dietary aflatoxin levels, which is in accordance with that reported by Tapia-Salazar et al (2012) for L. vannamei and by Boonyaratpalin et al (2001) and Gopinath and Raj (2009) for P. monodon fed contaminated diets (from 15 to 2500 µg aflatoxin kg -1 diet).…”
Section: Dietary Aflatoxinsupporting
confidence: 81%
See 2 more Smart Citations
“…Reduction in feed intake might be caused by the presence of non-palatable compounds generated in the grain during mold growth. No reduction in survival was found in the present study using low dietary aflatoxin levels, which is in accordance with that reported by Tapia-Salazar et al (2012) for L. vannamei and by Boonyaratpalin et al (2001) and Gopinath and Raj (2009) for P. monodon fed contaminated diets (from 15 to 2500 µg aflatoxin kg -1 diet).…”
Section: Dietary Aflatoxinsupporting
confidence: 81%
“…The adverse effects on feed intake and growth observed in shrimp fed aflatoxin-contaminated diets are similar to those previously reported for other shrimp species (Boonyaratpalin et al 2001, Soonngam and Hutacharoen 2007, Tapia-Salazar et al 2012. Reduction in feed intake might be caused by the presence of non-palatable compounds generated in the grain during mold growth.…”
Section: Dietary Aflatoxinsupporting
confidence: 73%
See 1 more Smart Citation
“…El extracto libre de nitrógeno fue calculado por diferencia. La pérdida de nutrientes en agua marina fue estimada de acuerdo con la técnica documentada por Tapia-Salazar et al (2013). El contenido de cromo fue determinado utilizando el método descrito por Bolin et al (1952) …”
Section: Análisis Químicosunclassified
“…The bromatological composition of the ingredients, diets, and feces was determined as follows: AOAC methods 930.15, 990.03, 942.05, and 962.09B were used to determine the moisture, crude protein, ash, and fiber contents, respectively (AOAC 1997); the Soxhlet method was used to determine the lipid content (Tecator 1997); nitrogen free extract was calculated by difference; nutrient loss in seawater was determined according to Tapia-Salazar et al (2013); chrome content was determined according to the method described by Bolin et al (1952) and modified by Cruz-Suárez et al (2009); and amino acids were determined according to Llames and Fontaine (1994) and Fontaine (2003).…”
Section: Chemical Analysismentioning
confidence: 99%